2006
DOI: 10.1158/0008-5472.can-05-1469
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoinositide 3-Kinase/Akt Pathway: A New Target in Human Renal Cell Carcinoma Therapy

Abstract: Metastatic renal cell carcinoma is resistant to current therapies. The phosphoinositide 3-kinase (PI3K)/Akt signaling cascade induces cell growth, cell transformation, and neovascularization. We evaluated whether targeting this pathway could be of therapeutic value against human renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 62 publications
10
129
1
Order By: Relevance
“…Activation of PI3K/Akt regulates the function of a broad array of intracellular proteins involved in fundamental processes, including cell proliferation, cell death, cell motility/adhesion, cell transformation, and neovascularization (36,37). PI3K inhibition enhances chemotherapy-induced tumor cell apoptosis in cancer cells (20). Low levels of activated Akt are observed in human RCC cells (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of PI3K/Akt regulates the function of a broad array of intracellular proteins involved in fundamental processes, including cell proliferation, cell death, cell motility/adhesion, cell transformation, and neovascularization (36,37). PI3K inhibition enhances chemotherapy-induced tumor cell apoptosis in cancer cells (20). Low levels of activated Akt are observed in human RCC cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K inhibition enhances chemotherapy-induced tumor cell apoptosis in cancer cells (20). Low levels of activated Akt are observed in human RCC cells (20). Some important factors, including EGF, VEGF, and TGF-b, are involved in the tumorigenesis of human carcinoma through activation of PI3K/Akt signaling cascade (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanisms by which this pathway regulates NPC proliferation include mutations in PI3K, PTEN deleted from chromosome 10 (PTEN), and Ras oncogene, as well as EGFR amplification (6)(7)(8). Previous studies showed that PI3K/Akt/mTOR signaling is frequently activated in many cancers, including lung, gastric, renal, and ovarian cancers (9)(10)(11)(12), and inhibition of this pathway could increase radiosensitivity (8,(13)(14)(15)(16)(17)(18). NPC cell lines and tissues also overexpressed phosphorylated Akt (p-Akt; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Akt activation may be an early event in lung tumorigenesis (West et al, 2003). Recent studies reported that the inhibition of PI3K activity by LY294002 reduced human cancer cell growth in vivo and in vitro by apoptosis or G1 cell cycle arrest (Casagrande et al, 1998;Hu et al, 2000;Semba et al, 2002;Gao et al, 2004;Takeda et al, 2004;Sourbier et al, 2006).…”
mentioning
confidence: 99%